It was GREAT Program:: Enhancing Pro-Environmental Awareness, Knowledge and Action among Students using Participatory Action Research Approach - Muhammad Tamar; Syurawasti Muhiddin; Umniyah Saleh; Grestin Sandy; Puspa Akhlakul Karimah; Nurly Fatin Ramadhani; Adrian Susanto; Ardelia Eka Nurzalzabila (International Journal of Educational Administration, Management, and Leadership, 2025)
This study aimed to develop a program to increase pro-environmental awareness, knowledge, and behavior among students at SMAN X in Makassar using the Participatory Action Research (PAR) approach. GREAT began with preparation, socialization, and environmental ambassador (EA) inauguration, then continues with program implementation which consists of five pro-environmental activities, namely Collecting Inorganic and Organic Waste, Cool with Reusable Stuff, Nature Gift Day, Planting and Watering a Tree to Support Green Nature, Upcycling Unused Stuff. After the implementation, a closing ceremony and program evaluation were held through FGD and self-reflection form. Overall, despite certain shortcomings that require attention for future programs, GREAT has effectively heightened awareness, knowledge, and redirected students' intentions toward pro-environmental actions not only in school but also in family and public environments. Additional endeavours are necessary to overcome challenges identified in the planning and execution of forthcoming interventions in other contexts.